2006
DOI: 10.1074/jbc.m604628200
|View full text |Cite
|
Sign up to set email alerts
|

The Length of Peptide Substrates Has a Marked Effect on Hydroxylation by the Hypoxia-inducible Factor Prolyl 4-Hydroxylases

Abstract: Three hypoxia-inducible factor prolyl 4-hydroxylases (HIF-P4HsThe hypoxia-inducible factors (HIFs) 2 are master regulators of the transcription of more than 100 hypoxia-regulated genes and play central roles in cellular oxygen homeostasis. HIFs are heterodimers that consist of an oxygen-regulated ␣ subunit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 34 publications
11
98
1
Order By: Relevance
“…Regulation of all four HIF hydroxylases by the citric acid cycle intermediates fumarate, succinate and oxaloacetate was investigated, with the PHDs exhibiting negative regulation with all three. 49,50 FIH-1, however, was not inhibited by physiologically relevant levels of these compounds, and is thus unlikely to be regulated via metabolic pathway intermediates, possibly due to its more important role in other processes not directly related to cellular metabolism, including neural differentiation and vasculogenesis. Understanding of the regulation of FIH-1 expression and the consequences for HIF activity is limited and warrants further investigation.…”
Section: Regulation Of Fih-1mentioning
confidence: 96%
“…Regulation of all four HIF hydroxylases by the citric acid cycle intermediates fumarate, succinate and oxaloacetate was investigated, with the PHDs exhibiting negative regulation with all three. 49,50 FIH-1, however, was not inhibited by physiologically relevant levels of these compounds, and is thus unlikely to be regulated via metabolic pathway intermediates, possibly due to its more important role in other processes not directly related to cellular metabolism, including neural differentiation and vasculogenesis. Understanding of the regulation of FIH-1 expression and the consequences for HIF activity is limited and warrants further investigation.…”
Section: Regulation Of Fih-1mentioning
confidence: 96%
“…The most extensively studied prolyl hydroxylases are the ones that hydroxylate a proline residues in collagen molecules (8)(9)(10)(11)(12)(13). These studies reveal that the enzyme, isolated as a homogeneous protein by affinity chromatography from three different sources (8)(9)(10)12,14,15), occurs as a tetramer with a molecular weight of about 240,000 (11,(16)(17)(18). The enzyme does not hydroxylate free proline, and recognizes a conserved motif (LXXLAP in the HIF-1 molecule; X indicates any amino acid and P indicates the hydroxyl acceptor proline) in the primary substrate for hydroxylation (5,11,(19)(20)(21)(22).…”
Section: Regulation Of Prolyl 4-hydroxylase (Phd) Enzyme Activity Viamentioning
confidence: 99%
“…Indeed, biochemical in vitro studies revealed K m values of purified PHDs for oxygen close to the oxygen partial pressure (pO 2 ) in air, suggesting that the kinetics of specific HIFα hydroxylation under hypoxic conditions are rather slow (Ehrismann et al, 2006;Hirsilä et al, 2003). Of note, these K m values are critically dependent on the length of the target peptide (Koivunen et al, 2006). However, tissues in situ have to deal with a great variability of generally very low pO 2 values, even when the inspiratory pO 2 is considered to be "normoxic".…”
Section: Introductionmentioning
confidence: 99%